MEKANISME KO-KEMOTERAPI EKSTRAK ROSELLA (Hibiscus sabdariffa. L) DENGAN DOXORUBICIN PADA SEL KANKER SERVIKS (HeLa) SECARA IN VITRO - Daud, Intan; Hayu Nurani, Laela; Bachri, Moch. Saiful; Ariani Edityaningrum, Citra; Ma’ruf, Muhammad (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
Cervical cancer caused by exposure to Human Papilloma Virus (HPV) through sexual intercourse can be treated with Doxorubicin. Doxorubicin shows side effects so it needs to be combined with co-chemotherapy. Rosella (Hibiscus sabdariffa L.) The main content of anthocyanins is cytotoxic to HeLa cells.  The purpose of this study was to find co-chemotherapy combination of Doxorubicin and Rosella extract with apoptosis mechanism and Rosella antiproliferation.  The research method starts from the maceration process of Rosella petals using 96% ethanol. Cytotoxic test method, antiproliferation test, apoptosis, and combination test with MTT method using HeLa cells. The result of cytotoxic test showed IC50 of Rosella extract was 32.3 ± 2.15 µg/mL and IC50 of Doxorubicin was 2.68 ± 0.09 µg/mL. The antiproliferation test results in the control cell doubling time of 28.25 ± 0.21 hours while the concentration of Rosella extract at levels of 32.3; 16.15; and 8.08 µg/mL doubling time of 53.23 ± 0.20 hours, 39.02 ± 0.19 hours and 46.74 ± 0.23 hours so that it shows the inhibition of cell multiplication growth. The IC results show the combination of 4.04 µg/mL Rosella Flower Extract and 2.67 µg/mL Doxorubicin which is 0.0013 can be interpreted as a very strong synergistic effect (0.0013 ≤ 0.1). So it can be concluded the combination of ethanol extract Rosella flowers has antiproliferation properties through the mechanism of delaying the doubling time.